Kesiapan Guru Dalam Implementasi Kurikulum Merdeka (Studi Kasus Smp Negeri 137 Jakarta) - Nabilah Khonsa; Desy Safitri; Sujarwo Sujarwo (Journal on Education, 2023)
This study aims to test the readiness of teachers to implement the Independent Curriculum at SMP Negeri 137 Jakarta. Merdeka Curriculum is an innovative program that includes project-based learning, skills and character development, and a flexible curriculum structure. This study uses a descriptive research method with a quantitative approach. Respondents to this study were teachers at SMP Negeri 137 Jakarta, with the entire population (29 people) being the research sample. Data were collected through observation, interviews, questionnaires, literature studies and documentation. A closed questionnaire with a checklist of answer choices was used as a research instrument. The collected data were analyzed using descriptive data analysis techniques, including descriptive statistics to present data in percentage form using a relative frequency distribution. The results showed that teachers at SMP Negeri 137 Jakarta showed sufficient readiness in several aspects of the independent curriculum. Learning outcomes, indicators of success, and learning objectives are ready and can be implemented. The use and development of teaching tools, the implementation of the Pancasila Student Profile Strengthening Project, as well as the application of student-centered learning have also been carried out well. However, there are several aspects such as lesson planning and assessment that still need to be improved. In conclusion, the readiness of teachers in implementing the Independent Curriculum at SMP Negeri 137 Jakarta is quite good in many aspects. However, there are still several aspects that need attention and improvement to ensure the implementation of effective learning and in accordance with the independent curriculum.